2011
DOI: 10.1002/cncr.26731
|View full text |Cite
|
Sign up to set email alerts
|

Post‐treatment (not interim) positron emission tomography‐computed tomography scan status is highly predictive of outcome in mantle cell lymphoma patients treated with R‐HyperCVAD

Abstract: These data do not support the prognostic utility of PET-CT in pretreatment and interim treatment settings. A positive PET-CT after the completion of therapy identifies a patient subset with an inferior PFS and a trend toward inferior OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 41 publications
1
30
2
2
Order By: Relevance
“…Recent retrospective reports, however, suggest a relevance of PET in response assessment. [24][25][26] In our prospective study, a positive PET scan pretransplant was associated with a median PFS of ,2 years, significantly shorter than in the PET-negative cohort. The PETpositive PR group is of particular interest: according to the revised response criteria 27 , any PET-negative residual mass is compatible with CR.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Recent retrospective reports, however, suggest a relevance of PET in response assessment. [24][25][26] In our prospective study, a positive PET scan pretransplant was associated with a median PFS of ,2 years, significantly shorter than in the PET-negative cohort. The PETpositive PR group is of particular interest: according to the revised response criteria 27 , any PET-negative residual mass is compatible with CR.…”
Section: Discussionmentioning
confidence: 58%
“…In multivariate analysis (including MIPI-B, response by CT prior to transplant, and MRD after transplant), a positive PET scan before transplant was shown to be an independent predictor of PFS, EFS, and particularly OS. In retrospective studies, 25,26 a positive posttreatment PET scan also predicted early relapse. Our prospective PET-based results strongly suggest a value of this modality in the evaluation of response in MCL.…”
Section: Discussionmentioning
confidence: 96%
“…[13][14][15] In MCL, endof-treatment PET/CT is prognostic for PFS in non-transplant patients, both in a heterogeneously treated population and a population uniformly treated with R-HyperCVAD in the front-line setting. 16,17 The role of PET/CT continues to expand in the management of NHL, and despite prior uncertainty regarding its utility in indolent NHL, patients completing induction with chemoimmunotherapy and embarking on a maintenance regimen of rituximab who have a positive PET/CT appear to have inferior PFS at 42 months (32.9%) compared with PET/CT( À )patients (70.7%, Po0.001). 20 We present one of the first series to date evaluating the role of pre-transplant PET/CT in MCL.…”
Section: Discussionmentioning
confidence: 99%
“…16 In another series of MCL patients treated in the front-line with R-HyperCVAD without auto-SCT consolidation, a positive PET/CT at the conclusion of therapy was associated with a median PFS of 11.1 months, while the median PFS for patients with a negative PET/CT was not reached (P ¼ 0.0002). 17 Little is known, however, about the significance of PET/CT findings before auto-SCT in MCL. Therefore, we performed a retrospective study of patients with MCL and available pretransplant PET/CT at the Ohio State University (OSU) reviewed by a single nuclear medicine physician according to International Harmonization Criteria 18 to determine the association of PET/CT response with PFS and OS post auto-SCT.…”
Section: Introductionmentioning
confidence: 99%
“…Two strategies have been evaluated to appreciate the quality of response in MCL: functional imaging [positron emission tomography (PET)] and MRD assessment. Retrospective studies of PET following R-hyper-CVAD induction showed a significant association between posttreatment PET positivity and outcome, whereas interim PET was not predictive (60). PET negativity before upfront ASCT was associated with superior PFS and OS in MCL (61) but not if induction was R-CHOP only (ref.…”
Section: Assessment Of Quality Of Response To Predict Outcomes: Mrd Amentioning
confidence: 99%